Penerapan PHBS untuk Mengurangi Angka Stunting di GUO Kecamatan Kuranji Kota Padang Sumatera Barat - Dewi Yudiana Shinta; Melly Siska Suryani; Muhammad Diki Juliandi; Ikhwan Resmala Sudji; Abdul Rohman Wali (PELANTAR PRESS, 2025)
Stunting, or short stature in children, remains a significant problem in GUO Kuranji Padang. To address this issue, Clean and Healthy Living Behaviors (PHBS) have been implemented as a way to improve the quality of family life. PHBS encourages daily clean habits such as washing hands with soap, maintaining environmental hygiene, using healthy toilets, and consuming nutritious food. Through regular education and guidance, families in this area have begun to realize the importance of maintaining hygiene and good eating habits to prevent stunting. The involvement of community leaders and health cadres also helps to strengthen the sustainable implementation of PHBS. As a result, stunting rates have declined as children have become healthier and grown better. The PHBS program in GUO Kuranji shows that simple changes in habits can yield positive results. Continuous guidance and cooperation from all parties are essential for PHBS to become a permanent lifestyle that helps prevent stunting and improve the quality of community life